2016
DOI: 10.1080/09540121.2016.1161164
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating concepts of care in the HIV care continuum: ethnographic insights from the implementation of a “Universal Test and Treat” approach in South Africa

Abstract: South Africa currently sustains the largest antiretroviral treatment (ART) programme in the world. The number of people on ART is set to grow even more in the coming years as incidence remains stable, people on ART stay healthy, and guidelines for initiation become increasingly inclusive. The South African public health sector has increasingly relied on community-and home-based lay and professional "carers" to carry out the everyday tasks of rolling out the ART programme. Drawing on ethnographic research in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The average follow-up refers to the average time a study participant was observed in the context of the trial. strategies by the general population [29,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Trial Intervention Packagesmentioning
confidence: 98%
“…The average follow-up refers to the average time a study participant was observed in the context of the trial. strategies by the general population [29,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Trial Intervention Packagesmentioning
confidence: 98%
“…In the high-disease-burden and resource-constrained contexts of SSA, health workers experience a range of psychosocial stressors that leave them vulnerable to developing burnout, in many cases reducing service-quality as well as negatively impacting on their own health and wellbeing [ 12 ]. Health workers also face daily interpersonal, organizational, and structural threats to their mental wellbeing [ 9 , 10 ]. Caring for PLHIV may expose health workers to secondary, or associative, stigma simply through providing services to members of a stigmatized group [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…One study conducted in 2009 indicated that implementation of universal treatment in high prevalence sub-Saharan Africa (SSA) settings would require over 17,000 additional health workers and that to initiate universal access to treatment at CD4 cell counts of ≤ 350 cells/µl, South Africa alone would require a minimum of 6,300 additional health workers [5]. In addition to an expanded health workforce needed to support UTT, many qualitative studies report that health workers in SSA already see their current care targets as unattainable, with some compensating by using time outside of working hours as well as personal resources to deliver care to patients in need [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the high-disease-burden and resource-constrained contexts of SSA, health workers experience a range of psychosocial stressors that leave them vulnerable to developing burnout, in many cases reducing service-quality as well as negatively impacting on their own health and wellbeing [12]. Health workers also face daily interpersonal, organizational, and structural threats to their mental wellbeing [9,10]. Caring for PLHIV may expose health workers to secondary, or associative, stigma simply through providing services to members of a stigmatized group [13][14][15].…”
Section: Introductionmentioning
confidence: 99%